PENGAMALAN PENDIDIKAN ISLAM DALAM BERDEMOKRASI PADA MASYARAKAT - Irpan Riadi; Purniadi Putra (Fitrah, 2021)
This study aims to determine the practices carried out by the residents of Sebubus Village, Paloh District in democracy. This study uses a descriptive qualitative approach. The subjects of this study were residents of Sebubus Village, Paloh District, Sambas Regency. To obtain valid data accuracy in research using instruments; interview (interview) observation and documentation. The results of the study show that the perspective of practicing Islamic education in the 2019 Pilkades can be seen from the momentum of the village-level democratic party carried out by the organizers, especially the Pilkades committee formed by the Village apparatus or the Village Consultative Body (BPD). The practice of Islamic educational values in democracy is a form of brotherhood between fellow human beings (ukhuwah basyariyah), fellow religious people (ukhuwah diniyah), fellow Muslims (ukhuwah Islamiyah), and fellow citizens (ukhuwah wathaniyah).